Minister of Finance Reshuffle and the Purbaya Effect: A Reflection of Market Confidence and Indonesia’s Economic Stability through an Event Study Approach - Shinju Valentino Moksa; Yosua Parhorasan Manullang (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the reaction of the Indonesian capital market to the reshuffle of the Minister of Finance on 8 September 2025 and the appointment of Purbaya Yudhi Sadewa, known as the “Purbaya Effect.” Using an event study approach, abnormal returns of 45 LQ45 stocks are analyzed over an 11-day window (t−5 to t+5) around the announcement. Expected returns are estimated with a historical mean model, and abnormal returns are tested using one-sample t-tests, while differences between pre- and post-event periods are assessed with the Wilcoxon signed-rank test. The results show significant abnormal returns on several days, including a strongly negative reaction on the event day, followed by partial recovery in the post-event period. The significant difference between pre- and post-event abnormal returns indicates that the cabinet reshuffle had a material impact on market valuations. These findings provide empirical evidence of a “Purbaya Effect” and support the semi-strong form Efficient Market Hypothesis in the context of political shocks in an emerging market.